2006
DOI: 10.1590/s1516-35982006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência fotoquímica de gramíneas forrageiras tropicais submetidas à deficiência hídrica

Abstract: RESUMO -Neste estudo, as espécies capim-setária (Setaria anceps Stapf.), capim-hemárthria (Hemarthria altissima angolagrass. This showed that the increased capacity to dissipate the excessive energy to drive photosynthesis was satisfactory to maintain a low reduction state of the primary electron acceptor of the photosystem II (measured as qP). In general, ETR curves in response to increasing photosynthetic photon flux differed from control to stressed plants, especially for nilograss. In this species, a serio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…Silva et al (2006) comment that reductions in Fm can be related to the photoinhibition of the quinone, associating them to the inactivation of PSII in the membranes of the thylakoids, compromising the flow of electrons between the photosystems. Freire et al (2014) observed reduction in Fm from 2256 to 2048 in leaves of yellow passion fruit when irrigation water salinity increased from 0.5 to 4.5 dS m -1 , which is equivalent to a reduction of 9.2%, similar to that observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (2006) comment that reductions in Fm can be related to the photoinhibition of the quinone, associating them to the inactivation of PSII in the membranes of the thylakoids, compromising the flow of electrons between the photosystems. Freire et al (2014) observed reduction in Fm from 2256 to 2048 in leaves of yellow passion fruit when irrigation water salinity increased from 0.5 to 4.5 dS m -1 , which is equivalent to a reduction of 9.2%, similar to that observed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the activity of chlorophyll has been analyzed to understand the changes in photosynthesis caused by biotic or abiotic stresses, such as temperature (Oliveira et al, 2002), radiation (Mazza et al, 2000), water deficiency (Silva et al, 2006), salinity (Belkhodja et al, 1994), presence of insects (Bown et al, 2002) and herbicides (Ferreira et al, 2015). According to Baker and Rosenqvist (2004), under the effect of herbicide the reduction of chlorophyll activity occurs due to the reduction in the capture efficiency of the excitation energy by the reaction centers opened by PS II, which generates reduction in the quantum yield of the electron transport.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…Matos et al (2010) credited the increase in the minimal fluorescence in Cicer arietinum under water restriction to the reaction center, showing that the greatest losses occur during the energy transfer from the antenna after excitation. Silva et al (2006) showed that the reduction in the Fm was observed in the non-irrigated water regime in both genotypes. They indicated in general the faulty photoreduction of quinone A (QA), the primary electron acceptor of photosystem II, which may be associated with PSII inactivation in the thylakoid membranes, directly affecting the electron flow between the photosystems.…”
Section: Variables Of Chlorophyll a Fluorescencementioning
confidence: 81%